The Effects of Creatine Supplementation in Resistance Trainers - A Literature Review (Research, Society and Development, 2021)
Creatine consumption can enhance the effects of resistance training, promoting physiological results that can interfere in a positive way, generating an increase in muscle strength, muscle hypertrophy and endurance. This article aimed to verify the main effects and benefits of creatine supplementation in resistance training practitioners. As for the methods for its elaboration, we sought to review the literature, qualitative, descriptive, from secondary documents to achieve the objective. It is concluded that creatine supplementation by resistance training practitioners may influence the physiological results in such a way as to improve muscle strength, cell hydration, increase in muscle mass and muscle endurance.